Un nuevo Oldfieldthomasiidae (Mammalia: Notoungulata) del Paleógeno de la provincia de Salta, Argentina - Powell, Jaime Eduardo (2009)
A new representative of the family Oldfieldthomasiidae from Northwestern Argentina, Dolichostylodon saltensis gen. et sp. nov., is described. The material was found in the Lumbrera Formation, above the “Faja Verde II”, at El Simbolar, Guachipas Department, Salta Province, Argentina. Dolichostylodon saltensis is defined by the following features: deciduous and permanent upper teeth similar to Ultrapithecus rutilans Ameghino, 1901, but with more triangular dP, more prominent paracone, without mesiolabial fossette and with dP3 presenting well developed metaloph. Upper molars with prominent parastyle and metastile. Column of metacone wider than in Colbertia lumbrerense Bond, 1981. Mesiolabial fossette absent, distolabial fossette relatively wide and shallow. Well developed and curved crochet, surrounding the distolabial fossette. Wide distal cingulum. Hypocone reduced in relation to the protocone. Labial sulcus not very pronounced. Lower molars with expanded entoconid, located close to the hypoconulid and presenting a reduced sulcus between both. Talonid valley deeper than in C. lumbrerense. This discovery constitutes the second species of Oldfieldthomasiidae for this Formation and the third for Northwest Argentina. Other materials assigned to Oldfieldthomasiidae have been reported from Antofagasta de la Sierra Catamarca Province) but they were referred to the genus Colbertia Paula Couto, 1952. This species shows morphological similarities with Ultrapithecus rutilans, of the “Barrancan” (Casamayoran) of Patagonia. Dolichostylodon saltensis seems to have closer relationship with the patagonic forms than with the non-Patagonian species of Oldfieldthomasiidae, despite its brachydont teeth.